Design of an Asynchronous Processor with Bundled-data Implementation on a Commercial Field Programmable Gate Array (Informatica, 2016)
In this paper, we propose a modeling method and a design ow to design asynchronous processors with bundled-data implementation on commercial Field Programmable Gate Arrays (FPGAs). The modeling method mainly concerns modeling of an asynchronous control circuit on commercial FPGAs. In addition to the use of a design environment provided by FPGA vendor, the design ow includes constraint generation, timing analysis, and delay adjustment to design asynchronous processor from a prepared model to FPGA programming. In the experiments, we design three asynchronous MIPS processors. Comparing with the synchronous counterpart, one of them reduces global cycle time which results in 13.8% performance improvement and another one reduces energy consumption 9.3% for a multiplication and 8.8% for a matrix multiplication.